Recent trends in the management of minor salivary gland carcinoma - Poorten, Vincent Vander; Hunt, Jennifer; Bradley, Patrick J.; Haigentz Jr, Missak; Rinaldo, Alessandra; Mendenhall, William M.; Suarez, Carlos; Silver, Carl; Takes, Robert P.; Ferlito, Alfio (Head & neck, 2014)
The current management of minor salivary gland cancer is reviewed. These malignancies often present as a submucosal swelling and have been reported at all anatomic subsites of the head and neck. Modern imaging is essential in evaluating the location and the anatomic extent of disease. An incisional or punch biopsy determines the histologic type and grade. Recent advances in molecular biology have yielded diagnostic and potential therapeutic targets that may change our treatment in the future. Complete resection is the treatment of choice. Unfortunately, given the proximity of essential structures, the need to balance functional and cosmetic with oncologic consequences can interfere with an adequate “clear margin.” The neck should be treated when there is evidence of regional metastasis or when subclinical metastatic risk exceeds 15%. Surgery alone cures most low‐stage, low‐grade tumors, all other stages and grades require postoperative radiotherapy. Systemic treatment for locoregional and distant failure remains disappointing. © 2013 Wiley Periodicals, Inc. Head Neck 36: 444–455, 2014